Prebiotic potential of enzymatically prepared resistant starch in reshaping gut microbiota and their respond to body physiology - Khan, Anum; Ali, Huma; Rehman, Ubaid Ur; Belduz, Ali Osman; Bibi, Amna; Abdurahman, Mujib Abdulkadir; Shah, Aamer Ali; Badshah, Malik; Hasan, Fariha; Kilic, Ali Osman; Ullah, Asad; Jahan, Sarwat; et al. (PLOS ONE, 2022)
The increase in consumer demand for high-quality food products has led to growth in the use of new technologies and ingredients. Resistant starch (RS) is a recently recognised source of fibre and has received much attention for its potential health benefits and functional properties. However, knowledge about the fate of RS in modulating complex intestinal communities, the microbial members involved in its degradation, enhancement of microbial metabolites, and its functional role in body physiology is still limited. For this purpose, the current study was designed to ratify the physiological and functional health benefits of enzymatically prepared resistant starch (EM-RSIII) from maize flour. To approve the beneficial health effects as prebiotic, EM-RSIII was supplemented in rat diets. After 21 days of the experiment, EM-RSIII fed rats showed a significant reduction in body weight gain, fecal pH, glycemic response, serum lipid profile, insulin level and reshaping gut microbiota, and enhancing short-chain fatty acid compared to control. The count of butyrate-producing and starch utilizing bacteria, such as Lactobacillus, Enterococcus, and Pediococcus genus in rat’s gut, elevated after the consumption of medium and high doses of EM-RSIII, while the E. coli completely suppressed in high EM-RSIII fed rats. Short-chain fatty acids precisely increased in feces of EM-RSIII feed rats. Correlation analysis demonstrated that the effect of butyrate on functional and physiological alteration on the body had been investigated during the current study. Conclusively, the present study demonstrated the unprecedented effect of utilising EM-RSIII as a diet on body physiology and redesigning gut microorganisms.